Identifikasi Potensi Obyek Wisata Pantai Bungin Pinungan - Jamila; La Ode Amaluddin; Andrias (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2022)
Based on data from the Muna Regency Tourism Office, in 2020 Bungin Pinungan Beach is 1 of the top 5 tourist destinations in Muna Regency. This study aims to identify the potential contained in the Bungin Pinungan Beach tourism object in Lakarama Village, Towea District, Muna Regency. The method used in this research is descriptive qualitative method with 20 informants. The data in this study were collected through observation, interviews and documentation. The results showed that the potential for Bungin Pinungan Beach tourism objects: 1) the potential for natural panoramas including the beauty of white sand, clear and blue sea water, geomorphological features in the form of hills extending around the mountains, there are many mangroves and coconut trees, and coral reefs; and 2) potential apounturirs include accessibility to Bungin Pinungan Beach which can only be accessed via sea crossing from the Tampo Ferry port with a travel time of 40 minutes and through the pier of Lainea Village with a travel time of ±15 minutes. Furthermore, the available facilities and infrastructure include viewing towers, gazebos, piers, inns, bridges, prayer rooms, public toilets, and parking lots.